2010
DOI: 10.1088/1742-6596/234/1/012008
|View full text |Cite
|
Sign up to set email alerts
|

Thin film nanocomposites based on YBCO with defects comprised of self-assembled inclusions

Abstract: Thin film nanocomposites based on YBCO with defects comprised of self-assembled inclusions Abstract. The critical current of YBCO superconducting coatings in external magnetic field can be enhanced by incorporating high density of extended nanometer-sized defects to act as pinning centers for magnetic vortexes. One particular variant involves the deposition superconducting film with columnar defects comprised of self-assembled BaZrO 3 , BaSnO 3 or BaHfO 3 nanoinclusions. Here we report the results of our study… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
3
0

Year Published

2011
2011
2018
2018

Publication Types

Select...
3

Relationship

1
2

Authors

Journals

citations
Cited by 3 publications
(4 citation statements)
references
References 11 publications
1
3
0
Order By: Relevance
“…In this paper we present our observations on the strained nature of BaZrO 3 (BZO), BaCeO 3 (BCO) and Y 2 O 3 inclusions in epitaxial YBCO matrix obtained by metal oxide chemical vapour deposition (MOCVD). Some previous observations were reported in earlier papers [12,13]. We argue that significant anisotropic strain observed in BZO, BCO and Y 2 O 3 is caused by unusually large shrinkage of the YBCO lattice along its c-axis at a low temperature oxygenation step.…”
Section: Introductionsupporting
confidence: 66%
See 3 more Smart Citations
“…In this paper we present our observations on the strained nature of BaZrO 3 (BZO), BaCeO 3 (BCO) and Y 2 O 3 inclusions in epitaxial YBCO matrix obtained by metal oxide chemical vapour deposition (MOCVD). Some previous observations were reported in earlier papers [12,13]. We argue that significant anisotropic strain observed in BZO, BCO and Y 2 O 3 is caused by unusually large shrinkage of the YBCO lattice along its c-axis at a low temperature oxygenation step.…”
Section: Introductionsupporting
confidence: 66%
“…The results of the x-ray study of YBCO films with different amounts of inclusions can be found in our earlier reports [12,13]. In this study we concentrate on two samples with 10 mol% (approximately 6 wt%) of either BZO or BCO addition.…”
Section: Resultsmentioning
confidence: 94%
See 2 more Smart Citations